2004
DOI: 10.1046/j.0902-4441.2003.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum syndecan‐1, basic fibroblast growth factor and osteoprotegerin in myeloma patients at diagnosis and during the course of the disease

Abstract: Pretreatment syndecan-1, bFGF and OPG levels were found to be increased at diagnosis. Syndecan-1 and OPG fluctuated according to MM activity. Elevated serum syndecan-1 and bFGF levels predicted short survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
1
21
1
10
Order By: Relevance
“…Surprising was our finding of only statistically limit difference of serum levels of syndecan-1 during complex evaluation of all three prognostic categories according to IPI and at tagetted comparison of index 1 vs 3. This finding appears exceptional with respect to previous numerous studies proved a significant relationship between serum levels of syndecan-1 and levels of β 2 -m 9,38,39,40 and MM prognosis MM 9,39,42,43 . Thus, serum levels of syndecan-1 do not clearly reflect tumour load and renal failure, nor many other biological aspects of the disease 9,10 .…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…Surprising was our finding of only statistically limit difference of serum levels of syndecan-1 during complex evaluation of all three prognostic categories according to IPI and at tagetted comparison of index 1 vs 3. This finding appears exceptional with respect to previous numerous studies proved a significant relationship between serum levels of syndecan-1 and levels of β 2 -m 9,38,39,40 and MM prognosis MM 9,39,42,43 . Thus, serum levels of syndecan-1 do not clearly reflect tumour load and renal failure, nor many other biological aspects of the disease 9,10 .…”
contrasting
confidence: 46%
“…Scudla, T. Pika, M. Budikova, P. Petrova, J. Bacovsky, K. Srovnalik, J. Minarik, K. Langova Syndecan-1 is also present in the myeloma microenvironment and acts to promote aggressive myeloma behaviour. Previous studies have demonstrated elevated levels of syndecan-1 in the serum of patients with MM and proved its negative prognostic importance and strong correlation between increased level of serum sCD 138 and tumour mass, as assessed by percent of bone marrow plasmacytosis (BMPC), β 2 -m and MM activity 38,39 . High levels of sCD 138 correlate with tumour mass and have a significant impact on the biology of MM by virtue of its pleiotrophic effects on the cell behaviour 38 .…”
mentioning
confidence: 99%
“…Literature reports three possible types of results: low levels of OPG, 2-4 high 5-7 and no difference with controls. 8 In MM patients, the levels of RANKL and RANKL/OPG ratio were more than two times higher than controls (p<0.001). This agrees with most other studies.…”
mentioning
confidence: 99%
“…This agrees with most other studies. 4,8,9 OPG shows a tendency to decrease in the advanced clinical stages (NS) and in high grade MBD (S). The lowest OPG level was measured in patients with severe bone lesions (4.26±0.36 pmol/L).…”
mentioning
confidence: 99%
“…It is considered to be one of the most important molecules in the multiple myeloma pathobiology 26 . Syndecan-1 appears to be a new important prognostic marker, also a possible parameter for discernment of monoclonal gammopathy of undetermined signifi cance and multiple myeloma 8,9,[27][28][29] . Detected correlation of FLC, K/L ratio and sFas levels is now more of the academical meaning which would be observed.…”
Section: Discussionmentioning
confidence: 99%